Electric Field Measurement of the Living Human Body for Biomedical Applications: Phase Measurement of the Electric Field Intensity - Ichiro Hieda; Ki Chang Nam (International Journal of Antennas and Propagation)
The authors are developing a technique for conducting measurements inside the human body by applying a weak electric field at a radio frequency (RF). Low RF power is fed to a small antenna, and a similar antenna located 15–50 cm away measures the electric field intensity. Although the resolution of the method is low, it is simple, safe, cost-effective, and able to be used for biomedical applications. One of the technical issues suggested by the authors' previous studies was that the signal pattern acquired from measurement of a human body was essentially different from that acquired from a phantom. To trace the causes of this difference, the accuracy of the phase measurements was improved. This paper describes the new experimental system that can measure the signal phase and amplitude and reports the results of experiments measuring a human body and a phantom. The results were analyzed and then discussed in terms of their contribution to the phase measurement.